Antibacterial properties of glycosylated surfaces: variation of the glucosidal moiety and fatty acid conformation of grafted microbial glycolipids. Issue 7 (29th July 2020) - Valotteau, Claire; Roelants, Sophie L. K. V.; Dasaiyan, Prabhu; Zibek, Susanne; Günther, Michael; Soetaert, Wim; Everaert, Bernd; Pradier, Claire-Marie; Babonneau, Florence; Baccile, Niki; Humblot, Vincent
Abstract : Glycosylated surfaces can display antimicrobial properties. Abstract : Glycosylated surfaces can display antimicrobial properties. It has been shown that sophorolipids can be used to develop biocidal coatings against Gram-positive and Gram-negative bacteria, but with a limited efficiency so far. Therefore, it appears necessary to further investigate the surface antibacterial activity of a broader set of structurally related glycolipids. The present work explores the influence of the glucosidic moiety (gluco-, sophoro-, cellobio-) and the fatty acid backbone (saturated, cis or trans monounsaturated). We show that the fatty acid backbone plays an important role: cis derivative of sophorolipids (SL) grafted onto model gold surfaces has better biocidal properties than saturated (SL0 ) and trans monounsaturated (SL t ) molecules, which appear to be inefficient. The number of glucose units is also a key factor: a one-third decrease in antibacterial activity is observed when having one glucose unit (GL) compared to two (SL). Sugar acetylation (SLa ) does not seem to have an impact on the biocidal properties of surfaces. These results are not limited to sophorolipids, with cellobioselipids (CL) leading to similar antibacterial observations.